2008
DOI: 10.1007/s10533-008-9262-z
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification and nitrous oxide effluxes in boreal, eutrophic river sediments under increasing nitrate load: a laboratory microcosm study

Abstract: Intact sediment cores from rivers of the Bothnian Bay (Baltic Sea) were studied for denitrification based on benthic fluxes of molecular nitrogen (N 2 ) and nitrous oxide (N 2 O) in a temperature controlled continuous water flow laboratory microcosm under 10, 30, 100, and 300 lM of 15 N enriched nitrate (NO 3 -, *98 at. %). Effluxes of both N 2 and N 2 O from sediment to the overlying water increased with increasing NO 3 -load. Although the ratio of N 2 O to N 2 increased with increasing NO 3 -load, it remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 59 publications
(54 reference statements)
4
33
4
Order By: Relevance
“…3a and 4). An increase in N 2 O saturation with a decrease in salinity was reported in several estuaries (Berounsky and Nixson, 1993;Bange, 2006;Silvennoinen et al, 2008;Zhang et al, 2010). Similarly, N 2 O saturation showed an inverse relation with dissolved oxygen saturation (r 2 00.30; p B0.05; Fig.…”
Section: Spatial and Temporal Variations In N 2 O Concentrations In Tsupporting
confidence: 55%
“…3a and 4). An increase in N 2 O saturation with a decrease in salinity was reported in several estuaries (Berounsky and Nixson, 1993;Bange, 2006;Silvennoinen et al, 2008;Zhang et al, 2010). Similarly, N 2 O saturation showed an inverse relation with dissolved oxygen saturation (r 2 00.30; p B0.05; Fig.…”
Section: Spatial and Temporal Variations In N 2 O Concentrations In Tsupporting
confidence: 55%
“…The model was re-run 15 times with different randomly selected starting points for each diel time series. Model results where r 2 between modeled and observed data was >0.80 were averaged to obtain [Beaulieu et al, 2010a;Garcia-Ruiz et al, 1998b;Inwood et al, 2005;Kemp and Dodds, 2002;Martin et al, 2001;Richardson et al, 2004;Silvennoinen et al, 2008b] Increase [Silvennoinen et al, 2008b] Increase No effect [Beaulieu et al, 2010a] Increased ammonium Nitrification Increase [Kemp and Dodds, 2002;Strauss and Lamberti, 2000;Strauss et al, 2002] Decrease, or no effect [Jiang and Bakken, 1999] c Possible increase…”
Section: Dissolved Gas Fluxesmentioning
confidence: 99%
“…Previous studies have demonstrated that N 2 O production and emission from diverse rivers respond significantly to increasing anthropogenic N loading (Cole and Caraco, 2001;Garnier et al, 2006). Numerous investigations have reported strong correlations between dissolved N 2 O and NO 3 -concentration in river waters (Herrman et al, 2008;Silvennoinen et al, 2008). Yan et al (2012) concluded that NO 3 -is a valid predictor of river N 2 O production in a large-deep river.…”
Section: Introductionmentioning
confidence: 99%